Impact of Media-Induced Uncertainty on Mental Health: Narrative-Based Perspective - Kesner, Ladislav; Juríčková, Veronika; Grygarová, Dominika; Horáček, Jiří (JMIR mental health, 2025)
People worldwide are confronted with environmental and sociopolitical stressors that act as potent sources of subjective uncertainty. The uncertainty arising in response to the volatility and unpredictability of adversities is amplified by their representation or misrepresentation in media news. While the causal effect of media news on vicarious traumatization has been well established, we argue that the impact of negative media news is principally related to distress and anxiety stemming from the uncertainty-inducing effect of media representations of the state of the world. As a growing body of research suggests, minimizing uncertainty related to global stressors is a significant driver of media news use. However, extensive media exposure perpetuates stress and is associated with symptoms of psychopathology. The self-perpetuating vicious circle of worry and excessive media consumption has been amply confirmed by new research related to the COVID-19 pandemic. Furthermore, attempts to alleviate stress and anxiety stemming from uncertainties often result in maladaptive strategies. In particular, the adoption of rigid behavioral patterns may prompt various forms of socially detrimental behavior. Critical factors in prevention and remediation include limiting media overexposure and implementing therapeutic interventions that focus on increasing tolerance to uncertainty.
Keywords: Mental Health; Humans; úzkost; uncertainty; duševní zdraví; anxiety; lidé; social context; cognitive psychology; Anxiety; nejistota; Stress, Psychological; COVID-19; Uncertainty; psychický stres; hromadné sdělovací prostředky; stress; Mass Media; media news